Parent Role In Sex Education In Teenagers - Lestari, Widayati (2016)
ABSTRACT PARENT ROLE IN SEX EDUCATION IN TEENAGERS Widayati Lestari S300110017 Master of Psychology Universitas Muhammadiyah Surakarta, 2015 This study aims to describe how the role of parents in sex education and how parents' understanding of sex. The method used is qualitative method in the form of case studies, data collection, using interviews and observation. Subjects in this study were three sets of parents and three children. The conclusion is as follows: (1) An understanding of parents to include sex sex is related to biological and physical problems, psychological, cultural and moral, and social. (2) How to communicate the issue of sex in children can be done without any special time, by utilizing momentum, delivered with a complete, as well as starting the toddler age. Sex education is also given to adjust to the needs of the child and without beginning of an event. Submission submitted by sharing and interaction entwined in an intimate setting. (3) The role of parents in sex education, among others, the role of co- operation, the evaluator, pendididik, companion, and monitors in sexual issues. (4) sex education materials include differences in gender, etiquette, learn responssibility and sexual diseases. Submission of material is done in stages according to the development of children, (5) Children's positive responsse to sex education from parents because of an atmosphere conducive to reverse negative responsses because children are at a given moment is not appropriate sex education. Keywords: adolescents, the role of parents, sex education.